Towards a tobacco-free Americas: the importance of measuring progress - Carissa Etienne (Instituto Nacional de Salud Pública, 2017)
Tobacco use remains one of the eminently preventable causes of disease and premature mortality globally and in the Americas. It has been unequivocally established that there is no safe level of tobacco consumption,and the actions to be implemented to end the tobacco epidemic are well known...